Social dialogue at the national and European levels as a factor in the formation of a common labor and social policy - Getman, Anatolii; Yaroshenko, Oleg; Sereda, Olena; Maliuha, Lesya; Zhygalkin, Ivan (Society Register, 2023)
An important object of state policy is the regulation of social relations, i.e. a system of sufficiently stable and independent ties between individuals and social groups that are essential for the existence and functioning of society. The constitutional consolidation of Ukraine’s status as a social state implies the need to pursue an active policy to ensure the rights of all members of society to a decent living, social protection, participation in production management, maintaining a stable socio-economic situation, and mitigating social inequality. Therefore, the state’s social dialogue is a means of establishing a social compromise in society and a factor in the formation of a unified labor and social policy. The methodological basis of the study is several general scientific and special methods of cognition, the choice of which is determined by the peculiarities of its object, subject, purpose, and objectives. The purpose of the article is to clarify the theoretical, legal, and legislative characteristics of the concept of social dialogue from the perspective of their compliance with the current trends in the development of labor and legal doctrine, and to study the issues of social dialogue at the national and European levels as a factor in the formation of a common labor and social policy.